Expression of ADAMTS-7 in myocardial dystrophy associated with white muscle disease in lambs - Hi̇ti̇t, Mustafa; Yilmaz, Rahşan; Polat Di̇nçer, Peli̇n Fatoş; Yumuşak, Ni̇hat; Yi̇ği̇n, Akin (Polish Academy of Sciences Chancellery, 2018)
The aim of the present study was to investigate the role of ADAMTS-7 gene in the pathogenesis of myocardial dystrophy associated with white muscle disease (WMD) in lambs. A total of 217 cardiac tissue samples from lambs with WMD were used in the study. Histopathological sections of the samples were stained with hematoxylin-eosin (HE) and examined using Western-blot, real-time PCR (RT-PCR) and immunohistochemistry for ADAMTS-7 gene expression, and the findings were statistically evaluated. Histopathological examinations revealed fibrosis associated with hyalinization, necrosis and granular calcifications in cardiomyocytes. Western blot and RT-PCR showed a statistically significant upregulation of ADAMTS-7 (p<0.05) (p<0.05). Immunohistochemical analyses showed that immunopositive cell numbers significantly high for ADAMTS-7 (p<0.05). The study has revealed that ADAMTS-7 gene is significantly expressed in myocardial dystrophy associated with WMD in addition to its role in the pathogenesis of this disease.
Keywords: Gene Expression Regulation; White Muscle Disease; ADAMTS7 Protein; Animals; Humans; Genetic Predisposition to Disease; Cardiomyopathies